2018
DOI: 10.1039/c7sm02146a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of macromolecular crowding on RNA/spermine complex coacervation and oligonucleotide compartmentalization

Abstract: We report the effect of neutral macromolecular crowders poly(ethylene glycol) (PEG) (8 kDa) and Ficoll (70 kDa) on liquid-liquid phase separation in a polyuridylic acid (polyU)/spermine complex coacervate system. The addition of PEG decreased both the amount of spermine required for phase separation and the coacervation temperature (T). We interpret these effects on phase behavior as arising due to excluded volume and preferential interactions on both the secondary structure/condensation of spermine-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 102 publications
5
82
2
Order By: Relevance
“…However, more work is currently underway to further expand the field of phase-separated artificial cells and to combine these methods of forming phase-separated artificial cells with other existing models of cellular structure and function. For instance, recent work has explored the combination of associative phase separation within crowded solutions, more accurately recreating the environment under which coacervation may occur within cells [72]. The characteristics of polyuridylic acid/spermine coacervates were found to be dependent upon both the presence of macromolecular crowding and the identity of the crowding agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more work is currently underway to further expand the field of phase-separated artificial cells and to combine these methods of forming phase-separated artificial cells with other existing models of cellular structure and function. For instance, recent work has explored the combination of associative phase separation within crowded solutions, more accurately recreating the environment under which coacervation may occur within cells [72]. The characteristics of polyuridylic acid/spermine coacervates were found to be dependent upon both the presence of macromolecular crowding and the identity of the crowding agent.…”
Section: Resultsmentioning
confidence: 99%
“…polyanion [70]. Biologically derived molecules are still often used to model coacervates, such as the RNA polyuridylic acid ( polyU, a polyanion) and the cationic polyamine spermine [67,71,72]. In addition, synthetic polyelectrolytes have also been used.…”
Section: Associative Phase Separationmentioning
confidence: 99%
“…A second example where PEG promotes phase separation by association has been reported by the lab of Keating, who pioneered RNA-based complex coacervates as MLO model systems [ 122 , 123 , 124 ]. Marianelli and co-workers used coacervates formed from negatively charged poly-U RNA and positively charged spermine ( Figure 3 C), and studied the effect of macromolecular crowding on the phase transition using PEG (8 kDa) and Ficoll-70 (70 kDa) [ 122 ]. While PEG decreased the critical charge ratio between poly-U/spermine coacervates (similar to the examples in Section 4.1 ), this effect was negligible in the presence of Ficoll-70.…”
Section: How Does Crowding Affect Liquid–liquid Phase Separation?mentioning
confidence: 99%
“…Thus, the effect of PEG could not be explained by classical volume exclusion theory. Experiments with labelled Ficoll-70 and PEG revealed that only PEG was excluded from the coacervates, while Ficoll was enriched inside the dense coacervate phase [ 122 ]. Therefore, the enhanced phase separation effect of Ficoll cannot be attributed to crowding.…”
Section: How Does Crowding Affect Liquid–liquid Phase Separation?mentioning
confidence: 99%
“…Interactions other than electrostatic interactions have also been shown to modulate or even drive LLPS, including by cation-π 27 or hydrophobic interaction 28,29 . Complex coacervation is affected by many factors including ionic strength, pH, polyelectrolyte concentration, a balanced mixing ratio of oppositely charged polyelectrolytes, molecular weight of the polyelectrolytes, as well as temperature and the crowding pressure 30 . It is by now firmly established that CC, fundamentally and without specific biological driving factors, is an equilibrium state that can be described by a phase diagram 22,[31][32][33] .…”
mentioning
confidence: 99%